ADOPTING HEUTAGOGY IN NON-FORMAL EDUCATION: A PARTICIPATORY ACTION RESEARCH WITH COMMUNITY LEARNING CENTERS - Samnatha Gonzales; Carloz Fernandez; Li Wei (Yayasan Adra Karima Hubbi, 2025)
The rapid transformation in the demands of 21st-century competencies requires a shift in learning paradigms, particularly in non-formal education settings where learner autonomy and lifelong learning are central. Heutagogy, or self-determined learning, offers a promising approach to empower learners in community-based contexts. This study aims to explore the adoption of heutagogical principles in Community Learning Centers (CLCs) through a participatory action research (PAR) framework. The research was conducted in three CLCs across rural and urban areas, involving facilitators, learners, and community stakeholders as co-researchers. Data were collected through focus group discussions, reflective journals, and participatory observations over three action cycles. The findings reveal that implementing heutagogy in non-formal education fosters increased learner autonomy, critical reflection, and contextualized learning practices. Moreover, facilitators’ roles evolved from knowledge transmitters to learning partners, enhancing collaborative dynamics within the CLCs. The study concludes that heutagogy is not only feasible but also transformative in non-formal education, particularly when implemented through participatory and context-responsive strategies. This research contributes to expanding heutagogical practices beyond formal institutions and supports the development of learner-centered, adaptive educational models in marginalized communities.